Contrastive Analysis of Kinship Terms between Arabic and Indonesian Languages: Anthropolinguistic Study - Kholisin Kholisin; Rohma Maulidya; Muhammad Alfan; Moh. Fery Fauzi (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
Greeting words are the most widely used words in daily communication. Many greetings are taken from the kinship term. Each language has different kinship terms based on its culture. This study aims to describe (1) the Arabic kinship term, (2) the Indonesian kinship term, and (3) the similarities and differences between the Arabic and Indonesian kinship terms. This research is a qualitative research with contrastive and anthropolinguistic analysis approaches. The data of this research are the vocabulary of kinship terms in Arabic and Indonesian which are taken from various sources. The results are (1) Arabic kinship terms are more varied than Indonesian, (2) Arabic kinship terms have syntactic markers to distinguish between terms for male and female, (3) based on the patrilineal system applies to the Arab community, Arabic distinguishes between terms for father's line and mother's line, (4) in Indonesian, there are terms that are differentiated by age, (5) in terms of nature, the kinship term in Arabic is descriptive, while in Indonesian is descriptive and classified, (6) the terms of kinship in Arabic and Indonesian can be addressed to non-relatives so that both can be metaphorical.